Case Report: Pediatric Malignant Atrophic Papulosis With Small Bowel Perforation and Positivity of Anticardiolipin Antibody - Wang, Hai-Qing; Guan, Yu; Gong, Xiao-Pan; Chen, You-Tao; Ji, Chao (Frontiers in Pediatrics, 2021)
Malignant atrophic papulosis (MAP) is a life-threatening vasculopathy affecting skin, gastrointestinal tract, central nervous system, pleura membrane, and pericardium. MAP carries a poor prognosis primarily because of its systemic involvement. It is extremely rare in children. Herein, we report a pediatric case of MAP with small bowel perforation and anticardiolipin antibody positivity.